2022
DOI: 10.3390/biomedicines10051084
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Exposure of Musculoskeletal Tissue to Extracorporeal Shock Waves

Abstract: Extracorporeal shock wave therapy (ESWT) is a safe and effective treatment option for various pathologies of the musculoskeletal system. Many studies address the molecular and cellular mechanisms of action of ESWT. However, to date, no uniform concept could be established on this matter. In the present study, we perform a systematic review of the effects of exposure of musculoskeletal tissue to extracorporeal shock waves (ESWs) reported in the literature. The key results are as follows: (i) compared to the eff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 232 publications
0
17
0
Order By: Relevance
“…Additionally, it may also alleviate pain through hyperstimulation analgesia [ 32 ]. Applying ESWT stimulates the proliferation, migration, and differentiation of stem cells, fibroblasts, tenocytes, bone cells, and their precursors [ 33 35 ]. To understand the effects shown in this study, studies that show the direct influence of periosteal stimulation on orthotopic bone regeneration and the reduction of osteoclast activity through the inhibition of pro-osteoclastogenic factors could be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it may also alleviate pain through hyperstimulation analgesia [ 32 ]. Applying ESWT stimulates the proliferation, migration, and differentiation of stem cells, fibroblasts, tenocytes, bone cells, and their precursors [ 33 35 ]. To understand the effects shown in this study, studies that show the direct influence of periosteal stimulation on orthotopic bone regeneration and the reduction of osteoclast activity through the inhibition of pro-osteoclastogenic factors could be considered.…”
Section: Discussionmentioning
confidence: 99%
“…ESWT is a non-pharmacological and non-surgical treatment modality for a variety of musculoskeletal disorders [ 12 ]. The molecular and cellular mechanisms of action of extracorporeal shock waves (ESWs) on musculoskeletal tissue were addressed in more than 180 studies in the literature [ 13 ]. A key mechanism is the reduction of pain sensation and a blockade of neurogenic inflammation through the overstimulation of substance P nerve fibers [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The initial use of ESWs in medicine was in kidney stone fragmentation, but their application was quickly expanded to a variety of pathologies of the musculoskeletal system, such as the treatment of non-unions, tendinopathies, and soft tissue disorders [ 2 , 3 , 4 ]. A recent systematic review [ 5 ] revealed 100 studies that addressed the effects of ESWs on bone and cartilage tissue [ 6 , 7 , 8 ], 39 studies about the effects of ESWs on tenocytes or scar tissue [ 9 , 10 , 11 ], and 42 studies on muscle and nerve tissue [ 12 , 13 , 14 ]. No studies are present about the effects of ESWs on fascial tissues, nor if myofascial pain is considered a promising indication for their use [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although ESWs are already widely used in clinical practice, the mechanism of action underlying their biological activities is still not fully understood. A wide variety of effects at the molecular and cellular levels have been described to date, whereby the effects of ESWs differ in each case from the tissue treated [ 5 , 18 , 19 , 20 , 21 , 22 ]. From the review conducted by Wuerfel [ 5 ], it appears that the more demonstrated effects of ESWs are the increase of cell proliferations of both progenitor and differentiated cells, the ability to mimic the effect of capsaicin by reducing substance-P concentration and of botulinum toxin by destroying endplates in the neuromuscular junction, and the modulation of the releases of various cytokines and collagen type I fibers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation